Internationalization and digitalization: their differing role on grocer and non-grocer retailer performance - Batsakis, Georgios; Theoharakis, Vasilis; Li, Chengguang; Konara, Palitha (Elsevier, 2023)
This study investigates the interplay between two critical phenomena in retailing, i.e., internationalization and digitalization, while accounting for retail sector differences. On one hand, internationalization allows retailers to access a wider range of markets, and on the other, digital channel expansion enhances customer reach and convenience within international markets. More specifically, we examine the relationship between retailer internationalization and performance (I-P relationship), and how this relationship is contingent upon the idiosyncrasies of retail sectors (i.e., grocery vs. non-grocery), digitalization, and their combined effects. Building on the liability of foreignness perspective, we first argue that the I-P relationship is U-shaped, because internationalizing retailers initially incur greater costs in their international expansion owing to their unfamiliarity with foreign markets, but as their foreign presence increases, they benefit from greater market power, experience, and scale economies. Then, we contend that as grocers suffer from higher levels of liability of foreignness due to increased requirements for host country embeddedness, non-grocers benefit more from internationalization with any gains and losses further amplified by digitalization. Hypotheses are tested against a panel of the 234 largest international retailers in the world over a 21-year period (1997-2017) and findings support the conjectures.
Keywords: Internationalization and performance (I–P); digitalization; grocery vs non-grocery retailers; e-commerce